(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents a new class of functions between bitopological spaces called R-(τ_1,τ_2)-continuous functions. Furthermore, several characterizations and some properties concerning R-(τ_1,τ_2)-continuous functions are established.